Tumor-Acidity Responsive Polymeric Nanoparticles for Targeting Delivery of Angiogenesis Inhibitor for Enhanced Antitumor Efficacy With Decreased Toxicity - Cong, Xiufeng; Chen, Jun; Xu, Ran (Frontiers in Bioengineering and Biotechnology, 2021)
Various nanocarriers with tumor targeting ability and improved pharmacokinetic property have been extensively utilized to reduce the toxicity of existing clinical chemotherapeutics. Herein, we showed that by encapsulating angiogenesis inhibitor anlotinib into polymeric nanoparticles, we could significantly decrease its in vivo toxicity. The introduction of pH-responsiveness into the nanocarrier further enhanced its anti-tumor activity. Systemic administration of the anlotinib-loaded nanocarrier into mice bearing A549 and 4T1 subcutaneous tumor received a higher tumor growth suppression and metastasis inhibition without detectable side effects. This strategy offers a promising option to improve the patient compliance of anlotinib.